The mutual influence of cultures on the Great Silk Road as a model for the formation of a modern code of national identity - Abbasova, K.Ya. (KU Publ., 2021)
The article examines the modern features of the formation of culture as a factor in the acquisition of national identity and the preservation of national consciousness. The authors refer to the history of the interaction of cultures on the Great Silk Road as a worldview model that allows one to study the roots of our cultural history, understand the origins of distinctive spirituality, our national involvement in world culture. Using the methodology of the philosophy of culture, the authors show that by the example of the interaction of cultures on the routes of the Great Silk Road, it is possible to trace the processes of intercultural communication for one and a half thousand years, to see the diversity of peoples who took part in this grandiose exchange of the achievements of material and spiritual culture, to determine the main characteristics of modern cultural situations, as well as trends in the development of intercultural relations in the future. All these factors have a decisive influence on the formation of the modern code of national identity.
Ұлы Жібек жолындағы мəдениеттердің өзара əсері ұлттық бірегейліктің қазіргі заманғы кодын қалыптастыру моделі ретінде
Взаимовлияние культур на Великом Шелковом пути как модель формирования современного кода национальной идентичности
Keywords: philosophy of culture; national identity; national consciousness; interaction of cultures; cultural heritage; historical experience